Analisis Pengaruh Persepsi Kemudahan dan Kemanfaatan terhadap Minat Pelaku UMKM dalam Menggunakan QRIS Bank Syariah Indonesia - Aisyah Defy Rahmayani Simatupang; Achmad Firdaus Ramadhani (STES Islamic Village, 2023)
This study aims to investigate the impact of perceived ease of use and perceived usefulness of QRIS (Quick Response Code Indonesian Standard) in Bank Syariah Indonesia (BSI) on the interest of Small and Medium Enterprises (SMEs) in adopting QRIS BSI. Adopting a quantitative approach, the research employs the Structural Equation Modeling Partial Least Square (SEM-PLS) method with Smartpls 4.0 as the analytical tool. The variables analyzed in this research encompass ease of use (X1), perceived usefulness (X2), and the intention to use (Y) QRIS BSI. Data for this study are obtained through primary data collected via questionnaire distribution and secondary data sourced from BSI's working documents. The research sample comprises 71 respondents selected through purposive sampling technique, with the criteria of being BSI customers from the Tangerang Karawaci Kelapa Dua branch and Micro and Small Business Actors (SMEs) who have become QRIS Merchants. The findings demonstrate that ease of use exerts a significant positive influence on the intention to use QRIS BSI. Perceived usefulness significantly and positively impacts the intention to use QRIS. The R-Square value for this research stands at 0.896 or 89.6%, indicating that 89.6% of the variance in the intention to use QRIS BSI can be explained by the variables examined, while 10.4% is attributed to other unexamined factors. Notably, perceived usefulness emerges as an exogenous or dominant variable significantly influencing the intention to use QRIS BSI, with the highest total effect of 0.585 compared to perceived ease of use. The implications of these findings underscore the significance of perceived usefulness and ease of use in driving the adoption of QRIS BSI among SMEs. As such, BSI is encouraged to intensify its efforts in promoting the practical and beneficial aspects of QRIS usage to SMEs, fostering greater acceptance and adoption among micro and small business owners. This research contributes valuable insights to the body of knowledge on the factors influencing the adoption of QRIS BSI in the context of Shariah-compliant organizations in Indonesia, providing a foundation for further exploration and development in this area.